2018
DOI: 10.1093/femsle/fny146
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Staphylococcus species in dairy cows, workers and shared farm environments

Abstract: Dairy farming involves frequent contact among animals, workers and farm environments. To explore the Staphylococcus spp. diversity that occurs on dairy farms, a pilot study sampled dairy workers, cows and the farm environments from five farms, two organic and three conventional farms, in Washington State. Samples were taken from the nares and hands of consenting workers (n = 24), udders and nares of selected cows (n = 25) and representative environmental surfaces (n = 96) from each farm. To increase diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
11
0
3
Order By: Relevance
“…The bacteriological identification results of different Staphylococcus species isolated from different sources are similar to those Roberts et al [ 27 ] who identified 19 different Staphylococcus spp. isolates from animal and human samples, among which S. haemolyticus S. xylosus, S. saprophyticus , S. sciuri , S. succinus , S. chromogenes and S. aureus were the most prevalent.…”
Section: Discussionsupporting
confidence: 85%
“…The bacteriological identification results of different Staphylococcus species isolated from different sources are similar to those Roberts et al [ 27 ] who identified 19 different Staphylococcus spp. isolates from animal and human samples, among which S. haemolyticus S. xylosus, S. saprophyticus , S. sciuri , S. succinus , S. chromogenes and S. aureus were the most prevalent.…”
Section: Discussionsupporting
confidence: 85%
“…In this study Staphylococcus spp had the highest percentage occurrence of 23.8 % which may be associated with mastitis (Roberts et al, 2018). This was followed by E. coli (21.2 %) and Bacillus spp (12.6 %) while…”
Section: Discussionmentioning
confidence: 49%
“…The next, is Staphylococcus spp. According to Roberts et al [23], Staphylococcus spp were found on human, animal and environment. Olatunji et al [20] equally isolated S. aureus from cow's milk.…”
Section: Discussionmentioning
confidence: 99%